Herbal Lactagogum And Breastfeeding Mother's Breast Milk Production: A Sistematic Review - Dina Hanifa; Sri Rahayu; Isnu Kurnia Nugrahaeni; Noviyati Rahardjo Putri (Journal of Midwifery Science: Basic and Applied Research, 2021)
Background: Exclusive breastfeeding has a major contribution to the growth and development of toddlers, especially at 1,000 HPK. The coverage of exclusive breastfeeding in 2017 was still low at 35.7% compared to the WHO and the Ministry of Health's 2019 target which is 50%. One of the efforts to increase the coverage of exclusive breastfeeding is increase the quantity and quality of breast milk production, so as to increase the mother's motivation to give exclusive breastfeeding. Efforts to increase by using drugs / herbs are known as laktagogums. Lactagogum drugs are rarely known because they are relatively expensive. Therefore, the use of alternative lactogogum herbs derived from plants that can be consumed by breastfeeding mothers is very necessary. Objective: The purpose of this study was to analyze the herbal lactagogum on breast milk production. Methods: Literature review using the keywords laktagogum and herbs for breast milk production. Articles retrieved from Google Scholar, Science Direct, and Pub Med in the period 2009 to February 2019. In addition, relevant text books and guidelines were used to add further information or additional reports that were not identified in the electronic search. Results: Based on several experimental studies, it was shown that torbangun leaves, young papayas, moringa leaves, katuk leaves and banana buds contain chemical compounds that can stimulate the synthesis of prolactin and oxytocin to increase the production and secretion of breast milk. Conclusion: Lactagogum torbangun leaves, young papaya fruit, moringa leaves, katuk leaves and banana buds have a positive effect on increasing breast milk production. Keywords: herbs, lactagogum, breast milk production